DUTIES AND FUNCTIONS OF INTERNAL AND EXTERNAL AUDITORS OF SHARIA BANK - Marina Marina (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
The increase in the growth of sharia banking needs to be supported by the performance and existence of sharia auditors. This study aims to discuss the roles and competencies of Islamic auditors in supporting Islamic banking performance. This type of research uses a qualitative method, a descriptive approach with literature study data. The results of this study indicate that the competencies that must be possessed by sharia auditors include knowledge of Islamic law, fiqh muamalah, skills in accounting and auditing, as well as special characteristics as sharia auditors. These competencies are the key to maximizing the roles and competencies of sharia auditors in supporting the performance of Islamic banking. The roles of sharia auditors include independent auditors, internal auditors, and sharia supervisory boards. Sharia compliance testing on Islamic Financial Institution entities is part of the role of the sharia auditor.